The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/jmv.20980
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of renal transplantation in patients with positive pre‐transplant hepatitis B surface antigen

Abstract: The clinical outcomes of 2,054 renal recipients were examined retrospectively based on pre-transplant hepatitis B surface antigen (HBsAg) status to investigate the efficacy of lamivudine treatment in HBsAg positive recipients. Pre-transplant HBsAg positivity was documented in 66 recipients. The 10-year patient and graft survival rates in Ag positive group were significantly lower than those of Ag negative group (64.4/36.6% vs. 88.2/70.5%, respectively, P < 0.0001). Since 1997, lamivudine was used when hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…Chan et al (14) described 12 HBsAgϩ recipients who received lamivudine preemptively, i.e., when a increase in HBV DNA levels with or without elevation in aminotransferase levels were detected, had similar renal allograft recipient survival compared with HBSAgϪ controls in contrast to their HBVinfected recipients transplanted before lamivudine was available. Ahn et al (17) included transplants performed between 1979 and 2004 and found 10-year patient, graft, and death-censored graft survival were inferior in HBsAgϩve (n ϭ 66) compared with HBsAgϪve (n ϭ 1988) recipients. However, in 27 HBsAgϩve recipients who received lamivudine, 10-year patient overall and kidney death censored survivals were comparable with HBsAgϪve recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al (14) described 12 HBsAgϩ recipients who received lamivudine preemptively, i.e., when a increase in HBV DNA levels with or without elevation in aminotransferase levels were detected, had similar renal allograft recipient survival compared with HBSAgϪ controls in contrast to their HBVinfected recipients transplanted before lamivudine was available. Ahn et al (17) included transplants performed between 1979 and 2004 and found 10-year patient, graft, and death-censored graft survival were inferior in HBsAgϩve (n ϭ 66) compared with HBsAgϪve (n ϭ 1988) recipients. However, in 27 HBsAgϩve recipients who received lamivudine, 10-year patient overall and kidney death censored survivals were comparable with HBsAgϪve recipients.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study have revealed that 5 years patient and graft survival rates were similar between HbsAg(+) and HbsAg(-) patients (1). Ahn et al revealed that, 27 HbsAg(+) recipients' (who were treated with lamivudine) graft and patients survival rates were similar to the HbsAg(-) patients (16).…”
Section: Discussionmentioning
confidence: 92%
“…Some studies revealed that 5 years patient survival rate was worse in HbsAg(+) patients, while another study revealed that HbsAg positivity had no impact on patient survival rate (12)(13)(14)(15)(16). However, a study have revealed that 5 years patient and graft survival rates were similar between HbsAg(+) and HbsAg(-) patients (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations